Social work with lesbians and gay men - Brown, Helen Cosis; Cocker, Christine (SAGE, 2011)
Working with lesbians and gay men is a largely neglected area of social work practice. This book provides social workers and other professionals with an overview of a number of key challenges and concerns that play a significant part in the lives of lesbians and gay men. Despite positive changes in legislation, social work can still fail to meet the needs of lesbians and gay men, and remains a marginalised area in practice, research and teaching. This book promotes an understanding of these issues and proposes ideas for social work practice that are inclusive of lesbians and gay men in assessment and the provision of services. --Book Jacket.